Adoption and Impact of Climate-Smart Agricultural Practices Among Smallholders Farmers in the Niger Delta: The Role of Agricultural Extension Services (International Journal of Agricultural Extension and Education, 2025)
The study examined the role of agricultural extension services and looked at how  smallholder farmers in the Niger Delta adopted and used Climate-Smart Agricultural  (CSA) practices. Determining the sociodemographic qualities of farmers, estimating  the degree of CSA adoption, identifying influencing factors, assessing extension  service support, assessing the impact of CSA on livelihoods and resilience, and  identifying the difficulties extension services face were the specific goals. Structured  questionnaire, focus groups, and key informant interviews were used to gather  primary data from 360 smallholder farmers in the states of Bayelsa, Delta, and  Rivers. Descriptive statistics, correlation, multiple regression, and Propensity Score  Matching (PSM) were used to analyse the data. The findings showed that 40.8% of  farmers had a secondary education, 67.5% were men, and the majority were in the  productive age range of 30 to 59 years. More than 70% of them implemented CSA  techniques, such as crop rotation, the use of organic manure, drought-tolerant crops,  and integrated pest management. Education, farm size, credit, climate information,  training, and access to extension services all had a significant impact on CSA  adoption, according to regression analysis (R2 = 0.742, p < 0.01). The results of the  correlation showed that the adoption of CSA and the provision of extension services  were strongly positively correlated (r = 0.642–0.713). According to PSM results,  CSA adopters’ income (ATT = ₦58,770, p < 0.001) and resilience (ATT = 7.44, p
Keywords: Adoption, climate smart, agricultural practices, smallholders’ farmers and Niger Delta